Endowing Ferroelectric Properties of Tetragonal Lysozyme Crystals through C60 Doping - Renbin Zhou; Xuejiao Liu; Weihong Guo; Dachuan Yin (Crystals, 2024)
The inherent nonpolarity of tetragonal lysozyme crystals excludes a ferroelectricity response. Herein, we present a demonstration of achieving measurable ferroelectricity in tetragonal lysozyme crystals through C60 doping. Ferroelectric characterizations revealed that C60-doped tetragonal lysozyme crystals exhibited typical characteristic ferroelectric hysteresis loops. Crystallographic structural analysis suggested that C60 doping may induce a reduction in the overall symmetry of tetragonal Lys@C60, leading to the observed ferroelectricity response. Moreover, the introduction of C60 facilitates efficient electron transport inside the crystal and influences the polarization of Lys@C60, further contributing to the observed ferroelectricity response. This work verifies that C60 doping can serve as a simple strategy to bestow novel ferroelectric properties to non-ferroelectric lysozyme crystals, potentially rendering them suitable for biocompatible and biodegradable application in implantable and wearable bioelectronics.